2019
DOI: 10.3389/fchem.2019.00456
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Based Alloy Nanoframes: Syntheses and Applications in Fuel Cells

Abstract: Noble metal nanostructures are being used broadly as catalysts for energy conversion in fuel cells. To overcome the future energy crises, fuel cells are anticipated as clean energy sources because they can be operated at low temperature, their energy conversion is high and their carbon release is almost zero. However, an active and stable electrocatalyst is essential for the electrochemical reactions in fuel cells. Therefore, properties of the nanostructures greatly depend on the shape of the nanostructures. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 84 publications
(121 reference statements)
0
23
0
Order By: Relevance
“…The method needs to synthesize nanoparticles first, and then use segregation and etching to realize the preparation of nanoframes (Bahadori et al, 2020). In addition, it can also be obtained by template method and replacement method (Nosheen et al, 2019).…”
Section: General Effectmentioning
confidence: 99%
“…The method needs to synthesize nanoparticles first, and then use segregation and etching to realize the preparation of nanoframes (Bahadori et al, 2020). In addition, it can also be obtained by template method and replacement method (Nosheen et al, 2019).…”
Section: General Effectmentioning
confidence: 99%
“…3 Elements such as Ni, Ru, Co, Fe, and Cu in previous studies were found to have high ORR activity at the cathode without forming hydrogen peroxide when used as cocatalyst together with Pt to form a bimetallic catalyst. [4][5][6] Amongst the mentioned metals, Ni has acquired a lot of attention because of the high catalytic activity and its resistance to corrosion to form Pt-Ni alloys nanoframes. 7 Pt content in Pt-Ni could be decreased by converting solid nanostructures into hollow nanostructures with ultrathin walls forming Pt-rich skin nanostructures and controlled surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…7 Pt content in Pt-Ni could be decreased by converting solid nanostructures into hollow nanostructures with ultrathin walls forming Pt-rich skin nanostructures and controlled surface composition. 6 The advantage of hollow structures over solid particles is that reactants can interact with 3D interior and exterior surfaces in catalytic reactions, whereas Pt atoms in solid nanoparticles go unused because they cannot participate in electrocatalytic reactions. 8,9 Pt-Ni electrocatalysts with ultrafine nanostructures such as nanowire, octahedron, and nanoframes have shown great improvements in accelerating the sluggish ORR due to excellent morphology, good stability, and great surface area owing to their exclusive orientated sides.…”
Section: Introductionmentioning
confidence: 99%
“…These structures consider several morphologies or architectures, with a remarkable surface to volume ratio, which can introduce unexpected behavior in nanoscale solids. These particles can be synthesized in several shapes such as squares, cubes, and hollow systems 13 , 14 , among others. One of these novel structures is a nanoframe, a hollow nanocube, mainly synthesized with a template approach from inorganic materials like metals and magnetic systems 15 .…”
Section: Introductionmentioning
confidence: 99%